Comparison of anti-TNF and IL-inhibitors treatments in patients with psoriasis in terms of response to routine laboratory parameter dynamics. (17th February 2022) - Ataseven, Arzu; Temiz, Selami Aykut; Eren, Güllü; Özer, İlkay and Dursun, Recep
Abstract: Background: Biological agent treatments represent a relatively new field and their effects on routine laboratory parameters are not fully known as there has been little research in the area. In our study, we aimed to evaluate the differences between the two main biological treatment groups and their effects on routine laboratory parameters. Methods: Patients were enrolled when they had received treatment for more than six months with biological treatments between January 2013 and April 2020. The available data on routine laboratory parameters were collected by routine blood tests before the treatment, at three months, and at the final evaluation. Results: When the changes in routine laboratory parameters were evaluated by treatment, it was found that the NLR and CRP values decreased statistically significantly in the anti-TNF group compared to the IL inhibitor group. In addition, strong suppression of these inflammation parameters means strong suppression of the immune system response. In addition, AST, ALT, and creatinine values were found to be statistically significantly higher in the anti-TNF group compared to the IL inhibitor group. Conclusions: In our study, anti-TNF treatments are shown to be more effective in reducing inflammation parameters while IL antagonists are safer in terms of biochemical parameters.